Pengaruh Penegerian Madrasah Terhadap Manajemen Peningkatan Mutu Pendidikan di MAN 2 Manggarai, Nusa Tenggara Timur - Abdul Majir; Yohanes Kurniawan (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2020)
The government implements private madrasa in order to improve Islamic education services. The strengthening of the existence of madrasa is inseparable from the participation of stakeholders. Especially in the fields of managerial, human resources, and infrastructure. The combination of a traditional Islamic education system with a modern Islamic education system is an appropriate alternative policy. This study aims to describe the concept of education management in the madrasa, the role of stakeholders, and the influence of madrasa enforcement on the implementation of education quality improvement in Madrasah Aliyah Negeri (MAN) 2 Manggarai, East Nusa Tenggara. This research is a case study with an interpretive or post positivistic approach. The findings of this study are the establishment of madrasa has a positive effect on the madrasah management which is more transparent, accountable, collaborative, coordinative, and while maintaining the characteristics of madrasas. Cooperative Participation Management based on religiosity become model of education quality improvement in MAN 2 Manggarai.